Insectivorous Birds Are Attracted by Plant Traits Induced by Insect Egg Deposition - Mäntylä, Elina; Kleier, Sven; Lindstedt, Carita; Kipper, Silke; Hilker, Monika (Journal of chemical ecology, 2018)
Insectivorous birds feed upon all developmental stages of herbivorous insects, including insect eggs if larvae and adults are unavailable. Insect egg deposition on plants can induce plant traits that are subsequently exploited by egg parasitoids searching for hosts. However, it is unknown whether avian predators can also use egg-induced plant changes for prey localization. Here, we studied whether great tits (Parus major) and blue tits (Cyanistes caeruleus) are attracted by traits of the Scots pine (Pinus sylvestris) induced by pine sawfly (Diprion pini) egg deposition. We chose this plant - insect system because sawfly egg deposition on pine needles is known to locally and systemically induce a change in pine volatile organic compounds (VOCs), and tits are known to prey upon sawfly eggs. In dual choice laboratory experiments, we simultaneously offered the birds an egg-free control branch and a systemically egg-induced branch. Significantly more birds visited the egg-induced branch first. We confirmed by GC-MS analyses that systemically egg-induced branches released more (E)-β-farnesene compared to control branches. Spectrophotometric analyses showed that control branches reflected more light than egg-induced branches throughout the avian visual range. Although a discrimination threshold model for blue tits suggests that the birds are poor at discriminating this visual difference, the role of visual stimuli in attracting the birds to egg-induced pines cannot be discounted. Our study shows, for the first time, that egg-induced odorous and/or visual plant traits can help birds to locate insect eggs without smelling or seeing those eggs.
Keywords: Hymenoptera; Behavior, Animal; Insect egg deposition; borovice lesní; ovum; Ovum; Light reflectance; Host-Parasite Interactions; interakce hostitele a parazita; Pinus sylvestris; Olfaction; Volatile organic compounds; plynová chromatografie s hmotnostně spektrometrickou detekcí; Vision; Sesquiterpenes; seskviterpeny; Gas Chromatography-Mass Spectrometry; Animals; těkavé organické sloučeniny; zvířata; Volatile Organic Compounds; chování zvířat; spektrofotometrie; Passeriformes; Spectrophotometry; Terpenoids; Visual Perception; zraková percepce